Tumor Metastasis - Xu, Ke (IntechOpen, 2016)
Metastasis is the major cause of cancer-related death. It is a multistep process. The mechanism underlying metastasis is complicated and poorly understood. Recent advances in tumor metastasis research have led to improved diagnosis and clinical management of cancer. However, new strategies on metastasis treatment are urgently needed, especially the novel biomarkers discovery and targeted therapy. This book is designed to present the most recent advances in tumor metastasis.